IMPROVING STRATEGIES IN DEALING WITH WATER SUPPLY FULFILMENT AND GROUNDWATER CONSERVATION ( LEARNING FROM SUCCESSFUL POLICIES AND PRACTICES) - Sugiyono, - (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2013)
Despite facts of abundant water resources that appear in Indonesia, the reliability of water service is still far from satisfied level.